Thermal tolerance and acclimation limits in bull trout ( Salvelinus confluentus ) alevin - Brendan Maldonado; Travis Durhack; Andrew Chapelsky; Sarah E. Glowa; Analisa Lazaro‐Côté; Raven M. Bennett; Timothy Bartley; Neil J. Mochnacz (Journal of Fish Biology, 2026)
The critical thermal maximum ( CT max ) of bull trout ( Salvelinus confluentus ) alevin was measured after 3 weeks of acclimation to 4–21°C. CT max increased from 24.3 at 4°C to 26.7 at 9°C, plateaued between 9 and 12°C (26.9°C), and declined to 25.9°C at 15°C. Acclimation mortality increased above 12°C, reaching 53.7% at 15°C, and no fish survived at 18–21°C. Condition factor declined at ≥12°C. Results indicate bull trout alevin have limited acclimation capacity beyond 12°C and suggest high vulnerability to lethal stress in streams where temperatures exceed this threshold.